Wybrane aspekty językowe prośby w internecie - Naruszewicz-Duchlińska, Alina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The paper’s objective is to study the linguistic characteristics of a request, to indicate and describe the obligatory and facultative segments of a text as well as the constitutive elements of this act of speech adapted to specific conditions of network communication. The material has undergone philological analysis with the use of the tools of linguistic genology and textology. On the basis of individual examples, the most important components of this part of speech realized in virtual space have been defined – in the structural and pragmatic dimensions.